The Music of Multicultural America : Performance, Identity, and Community in the United States - Rasmussen, Anne K.; Lornell, Kip, 1953- (Book collections on Project MUSE., 2016)
"The music of multicultural America explores the intersection of performance, identity, and community in a wide range of musical expressions. Fifteen essays explore traditions that range from the Klezmer revival in New York, to Arab music in Detroit, to West Indian steelbands in Brooklyn, to Kathak music and dance in California, to Irish music in Boston, to powwows in the midwestern plains, to Hispanic and native musics of the Southwest borderlands. Many chapters demonstrate the processes involved in supporting, promoting, and reviving community music. Others highlight the ways in which such American institutions as city festivals or state and national folklife agencies come into play. Thirteen themes and processes outlined in the introduction unify the collection's fifteen case studies and suggest organizing frameworks for student projects. Due to the diversity of music profiled in the book--Mexican mariachi, African American gospel, Asian West Coast jazz, women's punk, French-American Cajun, and Anglo-American sacred harp--and to the methodology of fieldwork, ethnography, and academic activism described by the authors, the book is perfect for courses in ethnomusicology, world music, anthropology, folklore, and American studies"--